An investigation into the acceptability and viability of restorative approaches in Saudi schools - Alamoudi, Lina (2020)
Restorative Approaches are being embraced in more and more schools around the globe and principally in countries such as Australia, Canada, New Zealand, the UK, and the USA as a creative approach to improving students’ social and emotional wellbeing, reducing harmful behaviour, and preventing and resolving conflict. The literature further suggests that the implementation of Restorative Approaches improves the educational climate and enhances student educational outcomes. Although these approaches seem to have roots in Islam, to the researcher’s best knowledge, Muslim countries had not adopted them. Saudi Arabia’s Vision 2030 that includes educational reform, is a path for implementing new programmes and practices and therefore provides a fertile ground for introducing approaches that also align with this new vision. The current study is the first of its kind in Saudi Arabia as it seeks to determine whether or not Restorative Approaches are acceptable and feasible for teachers working in the Saudi educational context. Qualitative methods, built upon by a constructivist paradigm, are used to examine teachers’ perceptions of the underlying values and principles that underpin Restorative Approaches and to reveal the opportunities and barriers to implementing these approaches in Saudi schools. Data was collected by employing questionnaires, creating online threads, and conducting online group interviews. Thematic analysis of the data revealed several findings that are in line with previous research in the field. Average teacher ratings for the likelihood of intervention indicate that teachers were likely to intervene in all types of misbehaviour. These findings are in line with previous studies done in other countries about bullying intervention, which indicate that the teachers in Saudi Arabia recognize the importance of intervention and take responsibility for a positive school climate. These findings also reflect on the values of caring and safety held by the teachers in Saudi schools. Although there is a consensus among Saudi teachers on the acceptability of principles of Restorative Approaches, applicability seems to be somehow problematic. Concerns include parents' authoritative style, high-control school settings, meeting expectations of the Ministry of Education, and finally, the lack of time and space to embrace Restorative Approaches. Most of the participants, however, consider their schools to be constructive and positive cultures, and some teachers applying practices that seem to be compatible with Restorative Approaches. The majority of teachers also agree that punishment is only a temporary solution that brings about long-term negative impacts.